STRATEGIES FOR SUSTAINABLE GROWTH: ENHANCING ORGANIZATIONAL COMPETITIVENESS IN A DYNAMIC MARKET - Bekbaeva Feruza Bakhtiyarovna (Modern American Journals, 2025)
In today’s rapidly evolving market environment, organizations face constant challenges in maintaining and improving their competitive position. Sustainable growth strategies are critical to ensuring long-term success and resilience. This article explores key approaches and best practices for enhancing organizational competitiveness while aligning with principles of sustainability. It examines strategic planning, innovation, digital transformation, talent management, and stakeholder engagement as drivers of sustainable competitive advantage. Special attention is given to how organizations can adapt to changing market conditions and technological disruptions. The findings contribute to a deeper understanding of how sustainable growth can be achieved through an integrated and proactive approach.
Keywords: Sustainable growth, competitiveness, strategic planning, innovation, dynamic market, digital transformation, talent management, organizational resilience, market adaptation, stakeholder engagement.